2007
DOI: 10.1002/jbm.a.31288
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of fluorocarbon chain end‐capped poly(carbonate urethane)s as biomaterials: A novel bilayered surface structure

Abstract: Poly(carbonate urethane)s (PCUs) are usually considered as biostable elastomers for long-term implantation. However, their hydrolytic stability is still questionable. The biodegradation appears to be initiated by oxidative and hydrolytic substances released by inflammatory cells. Therefore, the biostability of polyurethane might be improved with control of surface structure to reduce inflammatory response. A new type of PCUs end-capped with perfluoro chains was synthesized to explore a new avenue. A fluorinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Both the PCU and FPCU‐A materials showed quite similar spectra after air, water, and PBS incubations as shown in Figures 7 and 8. And no absorbance assigned to the fluorocarbon tails was observed in FPCU‐A, which was in well agreement with a previous study 25. The differences between the two materials came from the oxidative treatments.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Both the PCU and FPCU‐A materials showed quite similar spectra after air, water, and PBS incubations as shown in Figures 7 and 8. And no absorbance assigned to the fluorocarbon tails was observed in FPCU‐A, which was in well agreement with a previous study 25. The differences between the two materials came from the oxidative treatments.…”
Section: Resultssupporting
confidence: 92%
“…Such phenomena have been attributed to the water repelling and low surface free energy properties of fluorocarbon chains 35. Our previous study has shown that the fluorocarbon tails of FPCU‐A could migrate to the surface and formed an extremely hydrophobic surface 25. This unique surface structure must have made some contributions to the low adhesion and less deformation of platelets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations